Engineered Lubricative Lecithin-Based Electrospun Nanofibers for the Prevention of Postoperative Abdominal Adhesion - Junhan Li; Hao Lin; Jinghua Li; Yi Wang (Pharmaceutics, 2024)
Background: Postoperative abdominal adhesion is a prevalent complication following abdominal surgery, with the incidence of adhesion reaching up to 90%, which may precipitate a range of adverse outcomes. Although fibrous membranes loaded with various anti-inflammatory or other drugs have been proposed for anti-adhesion, most of them suffer from drug-induced adverse effects. Methods: In this study, a lecithin-based electrospun polylactic acid (PLA) nanofibrous membrane (L/P-NM) was developed for the prevention of postoperative abdominal adhesion, utilizing the hydration lubrication theory. The loaded zwitterionic lecithin allows the nanofiber surface to strongly bind water molecules to create a hydration lubrication interface. Results: As the TGA results show, the content of bound water in the nanofibers increased significantly with the increase in the lecithin content. Tribological test results show that L/P-NM reached a minimum coefficient of friction (COF) of about 0.112. Additionally, the developed nanofibrous membranes possess favorable tensile property and biocompatibility. Rat postoperative abdominal adhesion model evaluation results demonstrated that L/P-NM possesses significant anti-adhesive performance, with an adhesion score of only 1. Conclusions: Therefore, this study offers a promising strategy for efficiently preventing abdominal adhesion.